Prevalence and Risk Factors of Musculoskeletal Disorders in Nurses in the Operating Room - Rista Tri Wulandari; Masfuri Masfuri; Tuti Herawati (Indonesian Journal of Global Health Research, 2026)
Work-related Musculoskeletal Disorders (WMSDs) are health problems affecting the musculoskeletal system caused by non-ergonomic working environments and may result in soft tissue damage. These conditions can lead to chronic pain and fatigue, particularly among operating room nurses, thereby compromising occupational safety and work performance. To determine the prevalence and risk factors of work-related musculoskeletal disorders among operating room nurses. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were used for article selection. The JBI Critical Appraisal Checklist was employed to assess methodological quality. Articles were retrieved from Scopus, EBSCO, Springer Nature Link, ScienceDirect, and ProQuest databases covering the period from 2016 to 2026 using full-text articles. Of the 1,819 articles initially identified, 10 studies were included in this review following a screening process based on predefined inclusion and exclusion criteria. Data were extracted using a standardized form that included study characteristics, prevalence rates, affected body regions, and reported risk factors of WMSDs. The extracted data were analyzed using a narrative synthesis approach by grouping findings according to prevalence and categories of risk factors, including individual, biomechanical, and organizational factors. The prevalence of WMSDs ranged from 45.9% to 92.5%, with lower back pain reported as the most common complaint, followed by neck, shoulder, waist, and knee discomfort. Risk factors associated with WMSDs include individual factors, biomechanical factors, and organizational factors. The risk of WMSDs is multifactorial in nature. Therefore, comprehensive and continuous ergonomic interventions are needed to reduce the risk of musculoskeletal disorders and improve the quality of life of operating room nurses.